2015
DOI: 10.1073/pnas.1514157112
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 5 activates guanine nucleotide exchange factor GIV/Girdin to orchestrate migration–proliferation dichotomy

Abstract: Signals propagated by receptor tyrosine kinases (RTKs) can drive cell migration and proliferation, two cellular processes that do not occur simultaneously—a phenomenon called “migration–proliferation dichotomy.” We previously showed that epidermal growth factor (EGF) signaling is skewed to favor migration over proliferation via noncanonical transactivation of Gαi proteins by the guanine exchange factor (GEF) GIV. However, what turns on GIV-GEF downstream of growth factor RTKs remained unknown. Here we reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
85
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 49 publications
6
85
1
Order By: Relevance
“…Although the published work led us to conclude that a main function of GIV is to orchestrate the migration-proliferation dichotomy by enhancing cell migration and inhibiting mitosis (9,11,12) and that GIV must dually couple to both Gαi and Gαs to orchestrate such dichotomy, several questions remained unanswered. For example, what determines GIV's preference for one or the other G protein, and how does dual coupling to Gαi and Gαs impact signals downstream of both G proteins and receptor tyrosine kinases and cellular responses to growth factors?…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Although the published work led us to conclude that a main function of GIV is to orchestrate the migration-proliferation dichotomy by enhancing cell migration and inhibiting mitosis (9,11,12) and that GIV must dually couple to both Gαi and Gαs to orchestrate such dichotomy, several questions remained unanswered. For example, what determines GIV's preference for one or the other G protein, and how does dual coupling to Gαi and Gαs impact signals downstream of both G proteins and receptor tyrosine kinases and cellular responses to growth factors?…”
Section: Significancementioning
confidence: 99%
“…Thus GIV is ubiquitously expressed (10), can be recruited to different subcellular compartments (reviewed in ref. 4), binds to both Gαi and Gαs (9)(10)(11), and affects a number of important physiologic and pathologic processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that in the case of the prototypical GEM GIV, sequential phosphorylation of 2 Ser residues that flank the bifunctional GEF/GDI motif on GIV by 2 kinases, CDK5 35 and PKCu, 36 ensures that GIV exerts its GEF and GDI activities on Gai and Gas, respectively, in a temporally and spatially segregated manner (Fig. 2).…”
mentioning
confidence: 99%
“…Schematic showing the spatially separated GEF and GDI actions of GIV-GEM on Gai and Gas, respectively. Upon EGF stimulation, activated CDK5 kinase phosphorylates GIV on S1674 35 , thereby turning 'on' its GEF function toward Gai. Subsequently, GIV is phosphorylated also at S1689 by PKCu 36 ; this phosphoevent turns 'off' GIV's GEF function, but turns 'on' its GDI function toward Gas.…”
mentioning
confidence: 99%